\(n\)-Tuple Fixed Point Theorem in Bi-Complete \(F\)-quasi Metric Space - Gandhi, Manjusha; Aserkar, Anushree (Communications in Mathematics and Applications, 2022)
In the present paper, two theorems are discussed, one is fixed point theorem and another is \(n\)-tuple fixed point theorem for a new contractive condition in bi-complete $F$-quasi metric space. Also, an example is given to validate the result.
Keywords: Quasi metric space; \(n\)-tuple fixed point; Bi-complete